PeutzJeghers syndrome: A case report and literature review - Lakhey, A; Shakya, H (Journal of Pathology of Nepal, 2014)
Peutz–Jeghers Syndrome is an autosomal dominant inheritedhamartomatous polyp. We present a case of a 5-year-old young boywith a history of per rectal bleeding and mass protruding out of the anus. Physical examination revealed presence of mucocutaneous pigmented lesions over the tongue, and few hamartomatous polyps protruding out of the rectum suggesting Peutz–Jeghers syndrome. The presence in early infancy of small, well-demarcated and dark-brown to blue-black lentigines on the lips,buccal mucosa and perioral skin, should alert the clinician to Peutz–Jeghers Syndrome. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11597 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 677-679